Public Speaking Training Strategies for Enhancing the Self-Confidence of Young Children - Reni Eliyanti; Siti Bahiroh (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This research aims to identify strategies for public speaking training in early childhood through the roles of parents, teachers, and the PAUD environment. Using a descriptive qualitative approach, data were collected through interviews with parents and teachers, supported by activity documentation. The results of the study show that a supportive parenting style, active parental involvement in accompanying children, and good communication between home and school are important factors in building children's self-confidence. The teacher's strategy, which emphasizes the process and allows children to perform to the best of their ability without pressure, also contributes to creating a safe and enjoyable learning environment. Activities in early childhood education (PAUD) such as storytelling, picture reading, and sharing experiences become the main means of developing children's speaking skills. Additionally, communication media such as WhatsApp and communication books are used effectively to align the roles of teachers and parents. This research concludes that public speaking training for early childhood runs optimally when supported by strong synergy between families and educational institutions with a contextual and sustainable approach.